2017
DOI: 10.1186/s12966-017-0531-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between store food environment and customer purchases in small grocery stores, gas-marts, pharmacies and dollar stores

Abstract: BackgroundPurchases at small/non-traditional food stores tend to have poor nutritional quality, and have been associated with poor health outcomes, including increased obesity risk The purpose of this study was to examine whether customers who shop at small/non-traditional food stores with more health promoting features make healthier purchases.MethodsIn a cross-sectional design, data collectors assessed store features in a sample of 99 small and non-traditional food stores not participating in the Special Sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 69 publications
(87 reference statements)
1
73
0
Order By: Relevance
“…When considering each category of food individually, we believe that this difference was primarily driven by greater numbers of fresh fruit and vegetables selected by the intervention food pantry patrons. This is consistent with research done by Caspi et al () that suggested that the sales of fresh fruits and vegetables increased when produce was easily available and visible from the store entrance. The amount of canned and frozen fruits and vegetables chosen from each food pantry was also assessed.…”
Section: Discussionsupporting
confidence: 92%
“…When considering each category of food individually, we believe that this difference was primarily driven by greater numbers of fresh fruit and vegetables selected by the intervention food pantry patrons. This is consistent with research done by Caspi et al () that suggested that the sales of fresh fruits and vegetables increased when produce was easily available and visible from the store entrance. The amount of canned and frozen fruits and vegetables chosen from each food pantry was also assessed.…”
Section: Discussionsupporting
confidence: 92%
“…The use of an electronic payment application also enables standardization in purchase data entry. In addition, manual recording is not only time-consuming and resource-intensive but also presents the risk of missed transactions, especially during busy hours [43,56,59,71,72,75,105]. Alia et al highlighted the potential for electronic application to collect purchase data in UPS [56].…”
Section: Discussionmentioning
confidence: 99%
“…Other farmers' market studies analyse self-reported use of government incentive programs, government incentive sales data or records of coupon redemption [61][62][63][64][65][66], self-reported amounts spent [67] or total sales [39]. Some studies on convenience stores use purchase data collected using these same methods [68][69][70][71][72][73][74][75]. Given technological advances and changing legal requirements [76] in tracking sales, point of sales (POS) terminals are starting to gain popularity in UPS.…”
Section: Introductionmentioning
confidence: 99%
“…A fundamental issue that emerged from this study is how can demand generation be increased so people will be motivated to patronize stores for these staple foods? A community makes a corner store go into business or go out of business, and increasing the supply of staple foods in stores will not necessarily increase the demand (Gittelsohn et al 2014a; Caspi, Lenk, and Pelletier et al 2017). Having a consistent customer base that would buy the perishable foods in the corner stores would alleviate much of the stocking pressures.…”
Section: Discussionmentioning
confidence: 99%